The Effect of Perceived Organizational Support, Organizational Commitment and Job Satisfaction On Employee Performance At Pt Putra Perkasa Abadi & Group - Aditya Rendy Artha; Yohanes Temaluru (Universitas Pamulang, 2022)
This study aims to determine the effect of perceived organizational support (X1), organizational commitment (X2) and job satisfaction (X3) on employee performance. The population in this study were all employees of PT Putra Perkasa Abadi & Group with Group Leader to Division Head positions totaling 845 people. Determination of the number of samples using Slovin's calculation with accidental sampling technique of 271 people. The analytical tool used in this research is multiple linear regression assisted by SPSS software for Windows V25. The results showed that (1) Perceived organizational support (X1) had a positive and significant effect on employee performance (Y), (2) Organizational commitment (X2) had a positive and significant effect on employee performance (Y), and (3) Job satisfaction ( X3) has a positive and significant effect on employee performance (Y).